A Diagnostic Model With IgM Autoantibodies and Carcinoembryonic Antigen for Early Detection of Lung Adenocarcinoma - Zhang, Xue; Li, Jiaqi; Wang, Yulin; Liu, Man; Liu, Fenghui; Zhang, Xiuzhi; Pei, Lu; Wang, Tingting; Jiang, Di; Wang, Xiao; Zhang, Jianying; Dai, Liping (Frontiers in Immunology, 2022)
IgM autoantibodies, as the early appeared antibodies in humoral immunity when stimulated by antigens, might be a kind of excellent biomarkers for early detection of lung cancer (LC). We aimed to develop a multi-analyte integrative model with IgM autoantibodies and traditional tumor biomarker which could be a valuable and powerful auxiliary diagnostic tool and might improve the accuracy of early detection of lung adenocarcinoma (LUAD). Customized protein array based on cancer driver genes was performed in the discovery cohort consisting of 68 LUAD patients and 68 normal controls (NCs), and 31 differentially expressed IgM autoantibodies were identified. The top five candidate IgM autoantibodies (AUC ranking) including TSHR, ERBB2, Survivin, PIK3CA and JAK2 were validated in validation cohort by enzyme-linked immunosorbent assay (ELISA), which included 147 LUAD, 72 lung squamous cell carcinoma (LUSC), 44 small cell lung carcinoma (SCLC) samples and 147 NCs. These indicators presented the diagnostic capacity for LUAD with area under the receiver operating characteristic curves (AUCs) of 0.599, 0.613, 0.579, 0.601 and 0.633, respectively (P < 0.05). However, none of them was found to have significant difference between SCLC and NC groups, and only IgM autoantibody against JAK2 expressed higher in LUSC than NC (P = 0.046). Through logistic regression analysis, with the five IgM autoantibodies and carcinoembryonic antigen (CEA), one diagnostic model was constructed for LUAD. The model yielded an AUC of 0.827 (sensitivity: 56.63%; specificity: 93.98%). The diagnostic efficiency was superior to either CEA (AUC: 0.692) or IgM autoantibodies (AUC: 0.698). Notably, the accuracy of this model in early stage LUAD reached 83.02%. In conclusion, we discovered and identified five novel IgM indicators and developed a multi-analytes model with IgM autoantibodies and CEA which could be a valuable and powerful auxiliary diagnostic tool and might improve the accuracy of early detection of LUAD.